Closing the loop? Assessing efficiency in advancing circular economy transitions in the EU-27 countries - Álvarez-Jiménez, Isabel María; Expósito-García, Alfonso; Sánchez-Toledano, Daniel David; Velasco, Francisco (Elsevier, 2026)
The transition to a Circular Economy (CE) is a central pillar of the European Union (EU)'s sustainability agenda, yet significant heterogeneity persists among Member States (MS) in achieving this objective. This study contributes novel insights by introducing a dynamic efficiency assessment that simultaneously captures progress in the development of CE sectors, resource circularity and the reduction of material dependency across EU MS. Methodologically, a dynamic Data Envelopment Analysis (DEA) framework is employed, integrating two alternative efficiency specifications, complemented by Malmquist productivity indices (MPI) to evaluate intertemporal performance. The model accounts for potential frontier crossovers, thereby reflecting heterogeneous technological trajectories across EU countries. Results reveal marked disparities in CE efficiency transitions, with leading countries such as Germany, Italy, and the Netherlands displaying the highest efficiency scores, driven by effective policy frameworks. These findings highlight the urgency of coordinated actions to accelerate the CE transition across EU MS by fostering innovation and targeted policy incentives as critical levers for closing the identified efficiency gaps.
Keywords: Economía circular; Eficiencia industrial; Unión Europea; Análisis Envolvente de Datos; Circular Economy; Efficiency assessment; DEA; Circular material use rate; Material footprint; European Union